Cholesterol contents in human adrenal tissue in case of different duration of a lethal trauma - Bilyakov A.M. (Морфологія, 2013)
Background. Among the systemic changes in trauma the primary importance has the activation of the hypothalamus-pituitary-adrenal system, and increase in hormones synthesis, such as glucocorticoids. Precursor for the synthesis of steroid hormones is the adrenal free cholesterol. Objective. To determine the quantitative cholesterol (free and membrane) content in adrenal tissue at different times after injury. Methods. Adrenal glands of people who died at different times after injury were divided into three groups: 1st – death immediately after the injury, 2nd – in a short period of time (from several to tens of minutes), and 3rd – after 1-2 hours. Cholesterol content was estimated after tissue homogenization with the help of petroleum ether. Results. It is determined that the amount of cholesterol in human adrenal tissue differs depending on duration of a lethal mechanical trauma. In comparison with a control group (those who died as a result of a sudden death) the cholesterol content in adrenal tissue of persons of the 1st and 3rd groups did not differ (р>0,05), but differs for the 2nd group (р<0,001). While comparing the cholesterol content in those who died as a result of a violent death it was revealed that it is different in persons of the 1st and 2nd groups (р<0,01), 1st and 3rd groups (р<0,05), and 2nd and 3rd groups (р<0,001). Conclusion. Obtained results could be used in criminalistics for determination the duration of trauma before death.